Mesenchymal stem cells for cartilage regeneration in dogs - Sasaki, Akari (World J Stem Cells, 2019)
Articular cartilage damage and osteoarthritis (OA) are common orthopedic diseases in both humans and dogs. Once damaged, the articular cartilage seldom undergoes spontaneous repair because of its avascular, aneural, and alymphatic state, and the damage progresses to a chronic and painful situation. Dogs have distinctive characteristics compared to other laboratory animal species in that they share an OA pathology with humans. Dogs can also require treatment for naturally developed OA; therefore, effective treatment methods for OA are desired in veterinary medicine as well as in human medicine. Recently, interest has grown in regenerative medicine that includes the use of mesenchymal stem cells (MSCs). In cartilage repair, MSCs are a promising therapeutic tool due to their self-renewal capacity, ability to differentiate into cartilage, potential for trophic factor production, and capacity for immunomodulation. The MSCs from dogs (canine MSCs; cMSCs) share various characteristics with MSCs from other animal species, but they show some deviations, particularly in their differentiation ability and surface epitope expression. In vivo studies of cMSCs have demonstrated that intraarticular cMSC injection into cartilage lesions results in excellent hyaline cartilage regeneration. In clinical situations, cMSCs have shown great therapeutic effects, including amelioration of pain and lameness in dogs suffering from OA. However, some issues remain, such as a lack of regulations or guidelines and a need for unified methods for the use of cMSCs. This review summarizes what is known about cMSCs, including their in vitro characteristics, their therapeutic effects in cartilage lesion treatment in preclinical in vivo studies, their clinical efficacy for treatment of naturally developed OA in dogs, and the current limitations of cMSC studies.